Impact of Airflow Limitation on Comorbidities and Postoperative Complications in Patients Undergoing Thoracic Surgery: A Retrospective Observational Study - Yoshimi, Kaku (Ann Thorac Cardiovasc Surg, 2016)
Purpose: To assess the frequency of airflow limitation (AFL), and the relationship between AFL and preoperative comorbidities or postoperative complications in patients who had undergone thoracic surgery. Methods: The medical records of patients who underwent non-cardiac thoracic surgery at our institution between August 1996 and January 2013 were retrospectively reviewed. On the basis of preoperative pulmonary function tests, patients were classified with those with FEV(1)/FVC <70% [AFL(+) group] or with FEV(1)/FVC ≥70% [AFL(−) group]. Patient characteristics, preoperative comorbidities and postoperative complications were compared between the groups. Results: Of the 3667 patients assessed, 738 (20.1%) were allocated to the AFL(+) group. AFL was an independent risk factor for three preoperative comorbidities: chronic obstructive pulmonary disease (odds ratio [OR]: 4.65), bronchial asthma (OR 4.30) and cardiac diseases (OR 1.41). Airflow limitation was also an independent risk factor for postoperative respiratory failure including long-term oxygen therapy (OR 2.14) and atelectasis (OR 1.90) in the patients who underwent lobectomy or partial resection of the lung. Conclusions: Our retrospective study revealed that careful attention needs to be paid to airflow limitation in patients who undergo non-cardiac thoracic surgery since it appears to be an important feature of preoperative comorbidities and to increase postoperative complications.